Antigua and Barbuda. Annual report 2007 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The year under review, 2007, presents the operation of the IICA Office in Antigua and Barbuda, presents the actions of the institute in IICA's contribution to the repositioning of agriculture and rural life, promotion of trade and the competitiveness of agribusiness, strengthening of agricultural health and food safety systems, promotion of sustainable management of natural resources, strengthening of rural communities from a territorial approach, introduction of technology for modernization of agriculture and rural life